The Effect of Reputation Shocks to Rating Agencies on Corporate Disclosures - Sethuraman, Mani (The Accounting Review, 2019)
ABSTRACT This paper explores the effect of a credit rating agency's (CRA) reputation on the voluntary disclosures of corporate bond issuers. Academics, practitioners, and regulators disagree on the informational role played by major CRAs and the usefulness of credit ratings in influencing investors' perception of the credit risk of bond issuers. Using management earnings forecasts as a measure of voluntary disclosure, I find that investors demand more (less) disclosure from corporate bond issuers when the ratings become less (more) credible. In addition, using content analytics, I find that bond issuers disclose more qualitative information during periods of low CRA reputation to aid investors in assessing credit risk. My findings are consistent with credit ratings providing incremental information to investors and reducing adverse selection in lending markets. Further, consistent with theoretical predictions, my findings suggest that managers rely on voluntary disclosure as a credible mechanism to reduce information asymmetry in bond markets.